A batalha político-midiática do movimento Brasil Livre: mídia, gênero e sexualidade como alvos da desinformação nas redes sociais - Freitas Filho, Alberto Rodrigues de (2019)
This paper proposes to analyze how a battle between the traditional mediators and the new mediators is established in the post-truth era, taking as example the political-media action of the Free Brazil Movement (MBL). By disseminating narratives in social media, identified with an ultraconservative ideology increasingly influential in the public sphere, the group gains visibility and followers in a context of culture war. Through discourse analysis, we sought to understand the motivations of the MBL, which was aimed at all those who proposed the progressive debate on gender and sexuality in the period covered by this research